Orthorexia Nervosa: Personality Traits and Family Traits - Shepetovskaya, E. (Psychological Prospects Journal, 2012)
he article is devoted to the problem of personal characteristics and family characteristics of orthorectics. Own research conducted on the group of Polish youth refers to problems outlined above. In research attended individuals manifested characteristics of orthorexia (N=29) and comparative group (N=27). Analysis included perceptions of family of origin and selected personality traits. Results indicate, that surprisingly people with orthorexia describe their families’ systems as more consistent and well coping with crises than families of people without orthorexia do. Generally no significant differences were shown between orthorectics and non-orthorectics for the characteristics of personality and family traits, besides the higher intensity of obsessive and compulsive traits. These results will be discussed.